2016
DOI: 10.1016/j.tjem.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anabolic androgenic steroid usage associated with acute coronary syndrome in bodybuilder

Abstract: IntroductionIt has been argued in current studies that anabolic androgenic steroids (AAS) are misused by a great number of bodybuilders and athletes. However, there is diverse and often conflicting scientific data on the cardiac and metabolic complications caused by the misuse of AAS. There may be various reasons for myocardial infarction (MI) with normal coronary arteries. However, for the majority of patients, the exact cause is still unknown.Case reportA 32 year-old male who was complaining about severe che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…[43,44] However, supraphysiological doses cause coronary spasm. Sonmez et al [45] reported a clinical case of a 32-year-old male who had severe chest pain and was admitted to the local hospital. He had been taking AAS (200 mg weekly) for 3 years for bodybuilding.…”
Section: Effects Of Aas On the Cardiovascular Systemmentioning
confidence: 99%
“…[43,44] However, supraphysiological doses cause coronary spasm. Sonmez et al [45] reported a clinical case of a 32-year-old male who had severe chest pain and was admitted to the local hospital. He had been taking AAS (200 mg weekly) for 3 years for bodybuilding.…”
Section: Effects Of Aas On the Cardiovascular Systemmentioning
confidence: 99%
“…Hernandez et al described a case of a 24-year-old man with a history of AAS abuse who suffered a cardiorespiratory arrest and was later found to have acute MI due to severe coronary atherosclerosis and superimposed acute occlusive thrombosis at the left main trunk and left anterior descendant [2]. Whereas another case described a 32-year-old man who had acute MI due to coronary spasm from AAS use as he was found to have normal coronary arteries on an angiogram [13]. A few other case reports described young men with AAS abuse who developed acute MI and was later found to have hyperhomocysteinemia [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…The documented evidence of the ability of AASs to increase blood thrombosis (5) may explain this event. In addition, although the vasospastic mechanism is less established as a factor in AASs-based AMI (15,16), it may possibly intensify the atherogenic or the thrombotic mechanisms of AMI in AASs users. In concordance with these data, AAS abuse has been identified to induce vascular and endothelial dysfunctions (17,18).…”
Section: Discussionmentioning
confidence: 99%